ON THE NATURE OF GREENSTONE BELTS IN THE PRECAMBRIAN - Grachev A.F.; Fedorovsky V.S. (My University, 1981)
At present there is considerable speculation concerning the origin of greenstone belts. They are compared with Phanerozoic geosynclines, fold belts, modern island arcs or with the rift structures formed above subduction zones in marginal seas.Four stages in greenstone-belt development can be determined (3.8-3.0, 3.0-2.6, 2.6-1.9 and 1.9 b.y. and younger). Sections of early greenstone belts contain all the essential features of the modern oceanic sequences. Their peculiarities are: great thickness, presence of jaspilites and scarce occurrence of very coarse clastics. On the contrary, the latter type of sediment is widespread in younger greenstone belts and in those of the last stage which are completely formed in continental environment.Whole rock chemistry of Precambrian volcanics (more than 1800 analyses all over the world) confirms that alkali-olivine basalts are absent till 1.9 b.y. and andesites are generally rare. Widespread type of Early Precambrian basalts are Ol-Hy and Q normative ones, showing close similarity to typical abyssal tholeiites. The presence of basaltic komatiites is not a unique petrochemical feature of volcanism in the Early Precambrian as one thinks. Now similar rocks have been found in Phanerozoic rift zones. There is no evidence suggesting significant shortening of initial crustal complexes and greenstone belts. These data along with slight metamorphism and above features can only be explained by the formation of greenstone belts in rifting environment. During the early stages (3.8-1.9 b.y.) the thickness of the protocrust was not more than 10–20 km. It allows us to understand the rare occurrence of intermediate volcanics at early stages of the Earth's evolution. In summary it is argued that in the Early Precambrian the spread of primitive oceanic lithosphere was not compensated by the consumption in subduction zones. Consequently, plate tectonics cannot explain the formation of the crust in the early history of the Earth.
Keywords: Precambrian; Precambrian; Докембрий